Optimasi Komposisi Makanan Untuk Keluarga Penderita Diabetes Melitus Menggunakan Algoritme Genetika - Azmi Makarima Yattaqillah; Imam Cholissodin; Budi Darma Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Indonesia ranks 6th in the number of people with diabetes mellitus in the world. Of the 10.3 million Indonesians who have diabetes only 36.3 percent are diagnosed. As a result, many people do not have the right diet. The family of people with diabetes mellitus means a family with at least one member suffering from diabetes mellitus. This family is one of the factors that can increase the risk of suffering from diabetes mellitus by two to six times. Unhealthy lifestyles are also a cause of diabetes mellitus which makes diabetes a disease that can be prevented by consuming the right food starting from daily food in the family. Things that need to be considered in the right diet is to determine the composition of the right food, namely how to optimize nutrition in foods consumed by people with diabetes mellitus. Genetic algorithms that have reliability in producing optimal output, can be utilized in the preparation of daily food composition. In this study used integer chromosome representation, extended intermediate crossover method, reciprocal exchange mutation method, and elitism selection method. The best solution is obtained using max generation of 709 generation; population size of 250 individual; crossover rate of 0,4; and mutation rate of 0,6. The results of the global analysis show the calorie content of the food composition of the system meets expert tolerance standards and on average system can save costs by 27,27%.